Gender differences in the boundary permeability between work and family roles - Ahmad, Aminah (Universiti Putra Malaysia Press, 1998)
The objective of this study is to determine if there are gender differences in the relative permeability between work and family boundaries. Using self-administered questionnaires data were gathered from 250 employees. Half of the employees consisted of nurses working in a hospital in Selangor, Malaysia and another half their husbands. The study found that there was no evidence of gender differences in the permeability of work and family boundaries indicating that the dynamics of boundary permeability between work and family roles are similar among females and males. However, the respondents, both females and males, reported that work interfered with family life more than family life interfered with work. These results suggested that work and family boundaries are asymmetrically permeable with family boundaries being more permeable than work boundaries. Implications for future research are discussed.